Bridging hope: Therapeutic communication education for families of people with mental disorders in Madulang Village - Wahyuningsih, Sri; Hidayat, Medhy Aginta; Bawono, Yudho; Fitriyah, Anis; Kholifi, Ahmad In’am (Community Empowerment, 2025)
Families of peoples with mental disorders (PWMD) in Madulang Village have a limited understanding of therapeutic communication, despite its crucial role in recovery. This community service initiative aims to enhance the understanding and application of therapeutic communication among families of PWMD. The method employed is group education involving the community service team, the Bina Insan Madulang Community Group, families, and PWMD. The materials cover the definition, techniques, and stages of daily therapeutic communication. The results indicate an improvement in families' understanding and application of therapeutic communication, leading to better mental health for PWMD, as evidenced by reduced relapse rates and increased social activity.